A New Parameterized Conjugate Gradient Method based on Generalized Perry Conjugate Gradient Method - Khalil K. Abbo; Nazar K. Hussein (Tikrit Journal of Pure Science, 2023)
A New Parameterized Conjugate Gradient Method based on Generalized Perry Conjugate Gradient Method is proposed to be based on Perry's idea, the descent condition and the global convergent is proven under Wolfe condition. The new algorithm is very effective for solve the large-scale unconstrained optimization problem